KEMAMPUAN SONKEIGO DAN KENJOUGO MAHASISWA SEMESTER VI TAHUN MASUK 2016 PROGRAM STUDI PENDIDIKAN BAHASA JEPANG UNIVERSITAS NEGERI PADANG - Novi Hardianti; Meira Anggia Putri (Universitas Negeri Padang, 2018)
This study discusses the keigo ability of sixth semester students in the year of 2016 Japanese Language Education Study Program, Padang State University. The purpose of this study was to determine the ability of keigo (sonkeigo and kenjougo) VI semester students in the year of 2016 2016 Japanese Language Education Study Program, Padang State University. The type of research used in this study is quantitative research with descriptive methods. The population in this study was the sixth semester students of the year of entry in 2016, the Japanese Language Education Study Program, Padang State University, amounting to 30 people. The sample in this study was the sixth semester students of the year of entry in 2016, the Japanese Language Education Study Program, Padang State University, amounting to 30 people. The data in this study are scores of students' sixth semester keigo ability test results in 2016 Japanese Language Education Study Program, Padang State University. Based on the results of the research conducted it can be concluded that the ability of keigo in general is in the